(untitled) (Linguist, 2026)
Inclusive Education and Teaching Arabic to the Deaf: Towards a Visual-Cognitive Model in the Era of Digital Transformation.This article addresses the complex challenge of teaching Modern Standard Arabic as a second language (L2) to Deaf individuals, who constitute a distinct linguistic and cultural minority with a signed language as their first language (L1). It critiques the persistent failure of traditional pedagogical models rooted in a medical "rehabilitative" perspective. The core problem lies in the fundamental mismatch between the auditory-linear nature of spoken/written Arabic and the visual-spatial-kinesthetic nature of sign language. This dissonance is neurologically grounded: the Deaf brain undergoes "cross-modal plasticity," becoming optimally adapted for visual-spatial processing. Furthermore, early "language deprivation" of a rich signed language critically undermines the biological foundation for acquiring any subsequent language.Consequently, the article argues for a paradigm shift away from auditory-based approaches (like phonics) and advocates for an integrated educational model built on four pillars: Formal recognition of sign language as the primary language of instruction and cultural identity. 1. Curriculum redesign centered on developing morpho-syntactic awareness as a visual-cognitive alternative to phonological awareness. 2. Leveraging the visual strengths of Deaf learners, informed by cognitive theories like the Dual Coding Theory. 3. Harnessing digital transformation as the essential medium to implement this model, utilizing technologies like Augmented Reality (AR) and generative AI to transform Arabic into an interactive, visual learning space. The article concludes that achieving linguistic equity in inclusive education for the Deaf necessitates reframing the central question from "How can we make the Deaf hear our words?" to "How do we communicate with a brain designed for vision?" True inclusion requires adapting the educational system to the learner’s nature, not vice versa.